2021
DOI: 10.1108/cg-09-2020-0377
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 response: students’ readiness for shifting classes online

Abstract: Purpose Coronavirus disease 2019 (COVID-19) pandemic has led education institutions to move all face-to-face (F2F) courses online across the globe. The purpose of this study was to investigate Indian students’ perception of readiness for this sudden shift and at the same time, report a possible approach of good institutional governance to respond to such an unprecedented crisis. Design/methodology/approach This study followed a mixed approach combining both quantitative (e.g. survey) and qualitative (e.g. in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 26 publications
5
46
0
Order By: Relevance
“…Impacts of e-assessment were found influencing students differently according to their gender, academic level, stream of study and economic condition. Boys were found having better perception than girls, postgraduates were found having better perception than graduate students, students of science and law streams of studies were found having better perception than the students of social science and humanities, and students from stronger economic background had better perception than students of lower economic background which agree with the findings of NSS (2018), and Kundu and Bej (2021) supporting deep digital divide and an unequal distribution of e-resources among different social strata.…”
Section: Students' Overall Perception Of E-assessmentsupporting
confidence: 84%
See 2 more Smart Citations
“…Impacts of e-assessment were found influencing students differently according to their gender, academic level, stream of study and economic condition. Boys were found having better perception than girls, postgraduates were found having better perception than graduate students, students of science and law streams of studies were found having better perception than the students of social science and humanities, and students from stronger economic background had better perception than students of lower economic background which agree with the findings of NSS (2018), and Kundu and Bej (2021) supporting deep digital divide and an unequal distribution of e-resources among different social strata.…”
Section: Students' Overall Perception Of E-assessmentsupporting
confidence: 84%
“…It is obvious that the COVID pandemic has a far-fetching effect on the global academic arena as well as in India (Kundu and Bej, 2021), and this investigation also endorses the authors' claims that COVID was instrumental in bringing positive changes among academics to accept e-learning and e-assessment. The COVID compulsions were really effective in making online education productive with an instant result.…”
Section: Coronavirus Disease 2019 Effects On Students' Perception Levelsupporting
confidence: 74%
See 1 more Smart Citation
“…Our findings are also in line with other studies (Kundu & Bej, 2021) where it was confirmed that online educational process resulted in less engagement from students as well as fear perception associated with the online shift. In fact, the preference was to use a hybrid approach that combines both face-to-face with online based education especially for freshman students as well as programs with hands-on components.…”
Section: Discussion Of Resultssupporting
confidence: 93%
“…Mittal et al (2021) presented a theoretical model based on a time-series to analyze several factors about of the adoption of online teaching at the time of the outbreak of COVID-19. Kundu and Bej (2021) studied the Indian students' perception of being ready for the sudden shift to online education. Authors also reported guidelines for institutional governance to respond to such situation.…”
Section: Related Workmentioning
confidence: 99%